The Good Place in Your Classroom: Recommendations for Teaching Management Ethics. (June 2023) - van Esch, Chantal; Tarr, Emily; Frye, John
The sitcom The Good Place can be used by management instructors to teach ethical frameworks and concepts. This series, familiar to many undergraduate students in the US, features a Professor of Ethics and Moral Philosophy who gives mini lectures applied to what the characters are experiencing. These mini lectures can be shown to undergraduates studying ethics in a full course or as a subsection of courses such as management, organizational behavior, or leadership. This article provides information on particular clips that management instructors can use, recommendations for discussion topics with prompts provided, and a comparative pedagogical analysis of using this resource.